Production of Red Chilli (Capsicum annum L.) Hybrid Seed, Curmiyeast Concentrate, and Compost Based on Dairy Farm Waste - Dwi Wahyuni Ganefianti; Endang Sulistyowati; Sigit Sudjatmiko (Badan Penerbitan Fakultas Pertanian (BPFP), 2023)
This experiment aimed to produce hybrid red chilli seeds, Curmiyeast- concentrate, and Bokashi compost based on a dairy farm. Red chilli G 3 and G 7 were used as parent stocks in preparing UNIB C H73 hybrid. The recommended time for crossing the red chilli was around 06.00- 10.30 in the morning. The ingredients of Curmiyeast- concentrate were rice brand, ground corn, soybean meal, palm oil, mineral mix, salt, and urea. At the same time, Curcuma xanthorrhiza and yeast were 2 and 1%, respectively, in a total of 100%. Curmiyeast- concentrate in this modified formula contained 15.22% crude protein, with the price of Rp. 8,515/kg and MIOFC of Rp. 78,470/head/day or Rp. 9,019/l of milk produced. Bokashi compost contained N, P, K, and C organic and a ratio of C/N (18.9) that fulfilled the standards of SNI 19-7030-2004.